Prevalence and pattern of soft‐tissue rheumatism in a rural community in South‐South Nigeria: A cross‐sectional survey. Issue 4 (27th October 2022) - Agbebaku, Folasade; Emorinken, Airenakho; Agbebaku, Solomon
Abstract: Background: Soft tissue rheumatism arises from the pathology of periarticular structures. They are marked by pain and disability. Epidemiological studies in sub‐Saharan Africa are sparse. This study aimed to determine the epidemiology of soft‐tissue rheumatism in a rural community in South‐South Nigeria. Methods: This was a community‐based, cross‐sectional study conducted from February to July 2017 in South‐South Nigeria among 319 participants using the Community Oriented Program for the Control of Rheumatic Diseases (COPCORD) methodology. Participants aged 18 years and older were included in the study. Subjects reporting positive musculoskeletal pain were examined for specific soft tissue rheumatism. The diagnosis was based on established criteria. Results: The mean age of the study population was 48.87 ± 19.58 years. The prevalence of soft‐tissue rheumatism was 11.0% (35/319). Soft tissue rheumatism was more prevalent in females (24, 68.6%) than in males (11, 31.4%). The most common form of soft‐tissue rheumatism diagnosed was adhesive capsulitis (20.0%), closely followed by rotator cuff tendinitis (14.3%), carpal tunnel syndrome (14.3%), and plantar fasciitis (14.3%). Age ( p  = 0.06), body mass index ( p  = 0.034), and dyslipidemia ( p  = 0.028) were significantly associated with the prevalence of soft‐tissue rheumatism. A significant disability index (HAQ‐DI ≥ 1) was recorded in 40.0% of participants with soft tissue rheumatism. Twelve (34.3%) participants with soft‐tissue rheumatism attributed the disorder to their work, and 74.3% used hospital‐prescribed medications for treatment. Conclusion: Soft‐tissue rheumatism is associated with a significant disability affecting activities of daily living. Factors associated with its prevalence include increasing age and obesity. Abstract : Prevalence and distribution of soft‐tissue rheumatism. Key points: The prevalence of soft tissue rheumatism in rural Nigeria is 11.0%. The commonest soft tissue rheumatic disorder found is adhesive capsulitis. Age, sex, and dyslipidemia have a significant association with soft tissue rheumatism. This study attempts to bridge the knowledge gap about soft tissue rheumatism in Nigeria due to the paucity of data, especially in rural regions.